2019
DOI: 10.1002/jcb.29309
|View full text |Cite
|
Sign up to set email alerts
|

miR‐125a suppresses malignancy of multiple myeloma by reducing the deubiquitinase USP5

Abstract: miR‐125a is a microRNA that is frequently diminished in various human malignancies. However, the mechanism by which impaired miR‐125a promotes cancer growth remains undefined. In this study, we investigated the role of miR‐125a in the proliferation and apoptosis of multiple myeloma (MM). To do this, we used MM tissue samples (from 40 anonymous patients), normal matched control samples, and five MM‐derived cell lines. We also established a mouse model of MM xenograft to explore the effect of overexpression of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…miR-125a targets ubiquitin-specific peptidase 5 (USP5) mRNA, an oncoprotein that enhances cellular deubiquitination and proteolysis. Highly expressed miR-125a significantly repressed tumor growth of MM and lowered USP5 expression in vivo [ 154 ]. miR-101-3p was down-regulated and survivin (BIRC5) was up-regulated in MM cells.…”
Section: Role Of Mirna In MMmentioning
confidence: 99%
“…miR-125a targets ubiquitin-specific peptidase 5 (USP5) mRNA, an oncoprotein that enhances cellular deubiquitination and proteolysis. Highly expressed miR-125a significantly repressed tumor growth of MM and lowered USP5 expression in vivo [ 154 ]. miR-101-3p was down-regulated and survivin (BIRC5) was up-regulated in MM cells.…”
Section: Role Of Mirna In MMmentioning
confidence: 99%
“…Another one indicates that lncRNA NEAT1 promotes M2 macrophage polarization, hence accelerating MM progression 13 . In addition, based on miRanda database analysis and previous studies, one of lncRNA NEAT1 target microRNAs is microRNA‐125a (miRNA‐125a), and miRNA‐125a is shown to suppress MM progression 14‐16 . According to these evidences and the result of our preliminary study with small sample size, which indicated that lncRNA NEAT1 was upregulated in MM patients compared with healthy controls, the hypothesis was raised that lncRNA NEAT1 was involved in MM development and prognosis via interaction with miR‐125a; however, the related research is limited.…”
Section: Introductionmentioning
confidence: 69%
“…miR-125a ( Figure 2) expression is low in MM cell lines and tissues in comparison to matching control cells and tissues (74). Overexpression of miR-125a in NCI-H929 and U266 MM cells decreases cell viability and colonyforming ability by promotion of apoptosis (74). Overexpression of miR-125a in a mouse xenograft model inhibits TG (74).…”
Section: Up-regulated Mirs With Efficacy In Myeloma-related In Vivo Mmentioning
confidence: 99%
“…Overexpression of miR-125a in NCI-H929 and U266 MM cells decreases cell viability and colonyforming ability by promotion of apoptosis (74). Overexpression of miR-125a in a mouse xenograft model inhibits TG (74). Ubiquitin-specific peptidase 5 (USP5) was identified as a direct target of miR-125a (74).…”
Section: Up-regulated Mirs With Efficacy In Myeloma-related In Vivo Mmentioning
confidence: 99%
See 1 more Smart Citation